PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi pada Warung Susu Segar (STMJ) Karangdoro Semarang) - Tri Hartini, 15.05.51.0167; Setiawan, Mulyo Budi (Students' Journal of Economic and Management, 2019)
This study aims to examine the effect of product quality, price, and location on consumer purchasing decisions at Warung Susu Segar (STMJ) Karangdoro Semarang. The sampling method used was purposive sampling, with the number of data processed as many as 100 respondents. The analytical method used is the validity test, reliability test, multiple regression analysis, F test and t test. Partially the results of this study indicate that product quality has a positive and significant effect on purchasing decisions, prices have a positive and significant effect on purchasing decisions, location has a positive and significant effect on purchasing decisions. Simultaneously product quality, price and location have a positive and significant effect on purchasing decisions.